Design of a nursing objective structured clinical examination of a first-year clinical practice program - Castro-Yuste,Cristina (2020)
ABSTRACT Objective: The aim of the present study was to design a content-valid nursing objective structured clinical examination attending a first-year clinical nursing practice program. Method: The examination was designed following a procedure based on the consensus of experts which was comprised of three phases: selection of the activities in which students should be competent according to the learning outcomes of the course, clinical case design, and integration of the clinical cases designed into the stations of the test. Results: Of the 44 surveys submitted for the design of the stations, 37 were answered, of which 31 respondents met the inclusion criteria of the panel of experts. The activities on which the experts reached the highest degrees of consensus were: basic physical assessment and monitoring of vital signs, assessment of hygiene and skin status, ability to develop care plans, management of safety principles in administration of medication and administration of oral medication. Based on the selected activities, the experts developed 20 clinical cases, from which a four-station nursing objective structured clinical examination was designed. Conclusion: The structured methodology based on the design of experts enabled the design of a content-valid objective structured clinical examination appropriate for the evaluation of the learning outcomes achieved by the students attending a clinical practice program.